Fertilizer efficiency of ammonium (NH4+) and nitrate (NO3-) by fertigation in shallot production - Mar'atus Sholihatul Amanah; Anas Dinurrohman Susila; Krisantini (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Agronomic practices in Indonesia mostly still use ammonium as the primary source of nitrogen (N), whereas ammonium concentrations at certain levels can cause plant toxicity. The selection of the suitable N form (NH4+ and NO3-), especially by the fertigation method, is expected to increase the efficiency of N fertilization. This research aimed to obtain the appropriate source of NH4+ and NO3- to increase production and efficiency of fertilization in shallots. The experiment used a non-factorial randomized complete block design with four replications and six nitrogen treatments: without N, ammonium sources (urea, ZA), nitrate source (calcium nitrate), and combination of ammonium and nitrate (NPK Mutiara 16-16-16, calcium ammonium nitrate). The fertilizer doses contain N in equivalent levels, i.e., 167.9 kg N ha-1. The results showed that ZA increased the chlorophyll content of leaves and N content of plant tissue, while calcium nitrate increased the size and weight (fresh and dry) of bulb per plant. The highest recovery and agronomy efficiency was obtained in the ZA application, while the highest physiological efficiency and partial factor productivity were in calcium nitrate. Therefore, nitrate has the potential for shallot cultivation because it can increase production without accumulation in the bulbs. Keywords: Allium cepa; drip irrigation; nitrogen fertilizer; nitrogen form; NUE